Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I'm reading through a calculation for $\displaystyle z\pi\cot(\pi z)=\pi iz+\frac{2\pi iz}{e^{2\pi iz}-1}$ which confuses me. It states $$ \begin{align*} z\pi\cot(\pi z) &= \pi iz+\frac{2\pi iz}{\sum_{k=1}^\infty\frac{(2\pi iz)^k}{k!}}\\ &= \pi iz+\frac{1}{1-(-\sum_{k=1}^\infty\frac{(2\pi iz)^k}{(k+1)!})}\\ &=\pi iz+\sum_{n=0}^\infty\left(-\sum_{k=1}^\infty\frac{(2\pi iz)^k}{(k+1)!}\right)^n\\ &=\pi iz+\sum_{k=0}^\infty\frac{B_k}{k!}(2\pi iz)^k \end{align*} $$ where $B_k$ is the $k$th Bernoulli number. I don't follow the last equality from the third to fourth line. How does it follow? Thanks.

share|cite|improve this question
Equation (4) looks like it's immediate from (1), while (2) and (3) don't seem to serve any purpose to me. Remark. Here's the generating function for the Bernoulli numbers. – anon Apr 16 '12 at 7:04
Oh, that makes it much easier to see. Thanks! – chklien Apr 16 '12 at 7:08

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Browse other questions tagged or ask your own question.